Міжнародний досвід законодавчого забезпечення гендерної рівності - Кушнир, Н. В.; Kushnyr, N. V. (Право і безпека. – 2017. – № 1 (64). – С. 93-98, 2017)
Проаналізовано міжнародний досвід законодавчого забезпечення гендерної рівності з метою імплементації міжнародно-правових норм в у українське національне законодавство. Наголошено на тому, що досягнення гендерної рівності більшою чи меншою мірою охоплює процеси реформування національних законодавств, а практичні результати можливі лише через створення правового забезпечення рівності, відповідних державних механізмів правового забезпечення та через активну участь громадянського суспільства в цих процесах.

The research of international guarantees of women rights is of great importance for Ukraine both in terms of the most complete performance of its international and legal obligations under their observance, and in terms of making possible propositions to improve these standards and the formation of effective measures for their implementation at the national level. Therefore, in order to implement international and legal norms into Ukrainian national legislation the author of the article has analyzed international experience of legislative provision of gender equality. The author has emphasized on the fact that gender equality more or less covers the processes of the reform of national legislations and the practical results are only possible through the establishment of legal equality guaranteeing, appropriate legal mechanisms of legal provision and through the active participation of civil society in these processes. All legal systems were primarily formed due to the great division of labor (increase of its productivity, the creation of excess product and the need of its fixing by certain holders, etc.). Best practices of more or less coherent scheme, structure of directions of implementing the gender principle within the norms of labor law, its compliance in real social relations and determining the measures to improve legal mechanisms of its provision requires the building of a system of views, their general model, the concept of forming the legal mechanism for the compliance with the principle of equal opportunities within the employment relationships, as the best achievements of mankind in the sphere of the rights, freedoms and legitimate interests of citizens are developed.

Проанализирован международный опыт законодательного обеспечения гендерного равенства с целью имплементации международно-правовых норм в украинское национальное законодательство. Отмечено, что достижение гендерного равенства в большей или меньшей степени охватывает процессы реформирования национальных законодательств, а практические результаты возможны только через создание правового обеспечения равенства, соответствующих государственных механизмов правового обеспечения и через активное участие гражданского общества в этих процессах.
International experience of legislative provision of gender equality
Международный опыт законодательного обеспечения гендерного равенства
Кушнир Н. В. Міжнародний досвід законодавчого забезпечення гендерної рівності / Н. В. Кушнир // Право і безпека. – 2017. – № 1 (64). – С. 93-98.
Кушнир Н. В. "Міжнародний досвід законодавчого забезпечення гендерної рівності." Право і Безпека 1 (2017): 93-98.
Kushnir, N.V. (2017), “International experience of legislative provision of gender equality” [“Mizhnarodnyi dosvid zakonodavchoho zabezpechennia hendernoi rivnosti”], Pravo i Bezpeka, No. 1, pp. 93–98.
Keywords: Міжнародне право .International Law. Международное право; Наукові публікації. Scientific publications. Научные публикации; міжнародний досвід; Україна. Ukraine. Украина; законодавче забезпечення; гендерна рівність; імплементація; трудові права; международный опыт; законодательное обеспечение; гендерное равенство; имплементация; трудовые права; international experience; legislative provision; gender equality; implementation; labor rights